Assessment of lateral and vertical tissue displacement obtained by the retraction cord and the Magic Foam® paste: a randomized controlled clinical trial - El Gawwad, Nermin Ahmed Abd; El Mahallawi, Omaima Salah El Din; Al Naggar, Gihan Abd El Hady (Brazilian Dental Science, 2023)
Objective: to assess the amount of vertical and lateral gingival tissue displacement and recovery obtained by aretraction cord and Magic Foam® paste. Material and Methods: twenty- two participants, requiring full coverageprosthesis in the anterior area, were prepared using a deep subgingival chamfer finish line, then randomly allocatedto the retraction cord group (Group RC, n = 11 teeth) or the Magic Foam® Paste group (Group FP, n = 11 teeth).The amount of lateral and vertical tissue displacement was measured by comparing the pre- and post- displacementcasts at three fixed points (midbuccal, mesial and distal) using a stereomicroscope. After two weeks, tissue recoverywas assessed by taking an impression using a double mix. The amount of tissue recovery was measured verticallyfrom the gingival margin to the bottom of the sulcus and by comparing the results to the pre-displacement records.Results: there was no significant difference in the vertical gingival displacement (P > 0.05). However, there wassignificantly less lateral gingival displacement of the Magic Foam® Paste in the mesial and mid-buccal surfaces only(P < 0.05). The Magic Foam® Paste showed significantly more tissue recovery than the retraction cord (P< 0.05).Conclusion: both the retraction cord and the Magic Foam® Paste are considered effective means of retraction asthey give the least amount of retraction needed both laterally and vertically.KEYWORDSGingival retraction techniques; Gingiva; Retraction cord; Tissue recovery; Stereomicroscope.